2013
DOI: 10.1039/c3dt51403j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bis(N-arylcarboximidoylchloride)pyridine cobalt(ii) complexes and their catalytic behavior for 1,3-butadiene polymerization

Abstract: A new family of bis(N-arylcarboximidoylchloride)pyridine cobalt(II) complexes with the general formula [2,6-(ArN=CCl)2C5H3N]CoCl2 (Ar = 2,4,6-Me3C6H2, 4a; 2,6-(i)Pr2C6H3, 4b; 2,6-Me2C6H3, 4c; C6H5, 4d; 4-Cl-2,6-Me2C6H2, 4e) and a typical Brookhart-Gibson-type reference complex [2,6-(2,4,6-Me3C6H2N=CMe)2C5H3N]CoCl2 (5a) were synthesized and characterized. Determined by X-ray crystallographic analysis, complexes 4a, 4c-e, and 5a adopted a trigonal bipyramidal configuration, and 4b adopted a distorted square pyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…Interestingly, the introduction of strong electron-withdrawing substituents led to an increase of polymer yield (1d vs 1b) which might be owing to the enhanced electropositivity of the cobalt centre caused by the electron-withdrawing effect of trifluoroethoxy group. Similar results were observed in other Co(II)-based complexes36,37 . The incorporation of phenoxy substituent to the imine-carbon (1e) resulted in a slight decrease in polymer yield compared to the complexes with alkoxy groups (1a-1c).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the introduction of strong electron-withdrawing substituents led to an increase of polymer yield (1d vs 1b) which might be owing to the enhanced electropositivity of the cobalt centre caused by the electron-withdrawing effect of trifluoroethoxy group. Similar results were observed in other Co(II)-based complexes36,37 . The incorporation of phenoxy substituent to the imine-carbon (1e) resulted in a slight decrease in polymer yield compared to the complexes with alkoxy groups (1a-1c).…”
supporting
confidence: 89%
“…We recently reported that Co(II) complexes bearing bis(imino)pyridine 33 and α-diimine 34 ligands exhibited high catalytic activity and cis-1,4-selectivity for 1,3-butadiene polymerization, and quite interestingly, the addition of phosphines to these systems not only enhanced the catalytic activity but also switched the selectivity from cis-1,4-to 1,2-manner. 35 In these our previous reports, it was found that, for Gibson-type catalysts, the substituents on the C=N carbon position showed a large influence on the catalytic behaviors of the corresponding Co(II) complexes 36 . Furthermore, besides us, the effect of substituents at C=N carbon position on the catalytic behaviors of 1,3-diene polymerization were rarely investigated 37 and 2c were further characterized by single-crystal X-ray diffraction analysis, the selected bond distances and angles are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 96%
“…Advantage of electron-withdrawing substituents has been seen before in polymerization of butadiene by cobalt catalysts 43 and can be rationalised here as being due to a more electrophilic metal demanding more electron-density from the co-ordinated isoprene thus facilitating its attack by polymeryl chain-end. 1-3) were less active than those with single alkyls or uoro-substituents (4-7).…”
Section: Ligand Effectsmentioning
confidence: 57%
“…1 Using the above procedure, N,N′-bis(2,6-fluorophenyl)-2,6pyridinedicarboxamide was prepared in 78.5% yield (3.05 g, 7.85 mmol). 1 N,N′-phenyl-2,6-pyridinedicarboxamide (L3), 24 N,N′-bis(2,6dimethylphenyl)-2,6-pyridinedicarboxamide (L4), 25 N,N′bis(2,6-diethylphenyl)-2,6-pyridinedicarboxamide (L5) 26 and N,N′-bis(2,6-diisopropylphenyl)-2,6-pyridinedicarboxamide (L6) 27 were prepared using the above procedure and confirmed by NMR in according with the literature reports.…”
Section: General Considerationsmentioning
confidence: 99%